Online Harassment and Its Implications for the Journalist–Audience Relationship. Issue 8 (13th September 2020) - Lewis, Seth C.; Zamith, Rodrigo; Coddington, Mark
Abstract: Amid growing threats to journalists around the world, this study examines the nature of online harassment, the types of journalists most likely to experience it, and the most common forms of response to such abuse. Through a representative survey of U.S. journalists, we find that nearly all journalists experience at least some online harassment but that such harassment is generally infrequent overall and especially in its most severe forms. Nevertheless, online harassment against journalists disproportionately affects women (particularly young women) and those who are more personally visible in the news but not necessarily those who work for larger newsrooms. Moreover, it is clear that the more often a journalist is harassed online, the more likely they are to take a dim view of the audience by seeing them as irrational and unlike themselves, and to perceive interaction with them as less valuable. Additionally, as greater targets of the worst forms of abuse, women face a greater burden in deciding if and how to respond to online harassment. Conceptually, this article advances the literature on journalists and audiences by extending the concept of reciprocal journalism, which emphasizes individual-level perceptions that shape the quality of person-to-person exchanges. We explore how the experience of online harassment may complicate the way that journalists think about and act toward their audiences, offering a window into the downsides of encountering audiences online.